Tannin, protein contents and fatty acid compositions of the seeds of several Vicia L. species from Turkey - Kokten, Kagan; Kocak, Alpaslan; Bagci, Eyup; Akcura, Mevlut; Celik, Sait (Consejo Superior Investigaciones Cientificas-Csic, 2010)
The seedoils of six Vicia species (Leguminosae) were investigated for their protein, tannin contents and fatty acid compositions. The protein contents of the seeds were found to be between 21.87%-31.33%. The tannin contents of the seeds were found to be between 0.13%-1.07%. The fatty acid compositions of these six different species were determined by the GC of the methyl esters of their fatty acids. The oilseeds of Vicia species contain palmitic and stearic acids as the major component of their fatty acids, among the saturated acids, with small amounts of myristic, palmitoleic and margaric acids. The major unsaturated fatty acids found in the oilseeds were oleic, linoleic and linolenic acids. In this study, the total saturated fatty acids of Vicia species were between 18.5 and 22.4% while the total unsaturated fatty acids were between 71.1 and 80.3%.
Keywords: Fatty acids; Protein; Tannin; Vicia species